The impact of proximity to major central hepatic vasculature on perioperative outcomes and size-based risk stratification in hepatic hemangioma surgery - Yulin Xie; Hanrui Yang; Shiqi Lu; Guo Long; Xingyu Mi; Yilin Pan; Hongtao Yuan; Ledu Zhou (PLoS ONE, 2025)
Background and aim Surgical strategies for hepatic hemangiomas remain controversial, particularly concerning the influence of anatomical location and the use of tumor size thresholds. The proximity of tumors to major central hepatic vessels introduces significant surgical complexity and risks, yet its precise effect on perioperative outcomes and the appropriate application of size thresholds under varying anatomical conditions remain understudied. This study aims to evaluate the impact of proximity to major central hepatic vessels on perioperative outcomes and to assess the appropriateness of different size thresholds (8 cm vs. 10 cm) for risk stratification in varied anatomical contexts. Methods A retrospective cohort analysis was performed to evaluate hepatic hemangioma patients undergoing surgical resection from October 2016 to July 2024. The collected data included demographics, characteristics of the hemangiomas, laboratory data, surgical approaches, and perioperative variables. Patients were divided into group 1 (non-proximal) and group 2 (proximal) according to major central hepatic vascular proximity. Results A total of 309 patients were included in the study, with 176 in group 1 and 133 in group 2. The perioperative variables including operative duration, Intraoperative Blood Loss, postoperative stay, Intraoperative Transfusion Rate, postoperative complications grade and most postoperative laboratory tests showed significant differences between the two groups (P < 0.05). Group 2(proximal) increased intraoperative blood loss (+139 mL, P = 0.005), operative time (+60 min, P < 0.001), and complication risk (OR=2.44, P = 0.032) versus Group 1(non-proximal). ROC analysis further revealed that the utility of 8 cm and 10 cm as risk stratification thresholds varied significantly depending on tumor proximity. Conclusion The proximity of hepatic hemangiomas to major central hepatic vessels significantly elevates surgical difficulty and perioperative risks. Additionally, the sensitivity and specificity of 8 cm and 10 cm as surgical risk stratification thresholds varied distinctly depending on proximity to major central hepatic vessels.